Understanding the peak growing season ecosystem water‐use efficiency at four boreal fens in the Athabasca oil sands region. Issue 8 (10th August 2021) - Volik, Olena; Petrone, Richard; Kessel, Eric; Green, Adam; Price, Jonathan
Abstract: Ecosystem water‐use efficiency (WUE), a ratio between gross ecosystem production (GEP) and water loss through evapotranspiration (ET) can be helpful for the assessment of coupled peatland carbon and water cycles under anthropogenic changes in the Athabasca oil sands region (AOSR) where extensive oil sands development has been occurring since the 1960's. As such, this study assessed multiyear peak growing season variability of WUE at four fens (poor treed, poor open, treed moderate‐rich, open saline) near Fort McMurray using the eddy covariance technique combined with a set of environmental variables. Freshwater fens were characterized by WUE values within the range reported from other boreal wetlands while a saline fen had significantly lower values of WUE. Negative correlation (Rs  < −0.55, p  < 0.05) between WUE and net radiation was observed. Moisture conditions were responsible for interannual differences in WUE, whereby increasing WUE under wetter conditions was observed. However, such a pattern was offset by decreased air temperature (Tair ) resulting in moisture oversupply. This study also revealed a negative effect of wildfire on WUE due to a prominent decline in GEP and a moderate decrease in ET. WUE can be useful for monitoring the functioning of natural and constructed fens, but a better understanding of WUE variability under a wide range of climatic conditions with respect to differences in vegetation is required. Abstract : Multiyear peak growing season water use efficiency (WUE) a ratio between gross ecosystem production (GEP) and evapotranspiration (ET) is estimated at four boreal fens. The effect of environmental conditions of on WUE is analysed.